Mathematics
Wickedmama
42

solve using substitution or elimination. show work please. -2y=-4x-2 3x+2y=9

+4
(2) Answers
Collegegirl763

[latex]-2y=-4x-2 \\ \underline{3x+2y=9 \ \ \ \ \ } \\ -2y+3x+2y=-4x-2+9 \\ 3x=-4x+7 \\ 3x+4x=7 \\ 7x=7 \\ x=\frac{7}{7} \\ x=1 \\ \\ -2y=-4x-2 \\ -2y=-4 \times 1-2 \\ -2y=-4-2 \\ -2y=-6 \\ y=\frac{-6}{-2} \\ y=3 \\ \\ \boxed{(x,y)=(1,3)}[/latex]

scottyy

[latex] \left \{ {{-2y=-4x-2\ \ | add\ 4x} \atop {3x+2y=9\ \ \ \ \ \ \ \ }} \right. \\\\ \left \{ {{-2y+4x=-2} \atop {2y+3x=9}} \right. \\+----\\ add\ both\ equations\\\ 7x=7 \ \ | divide\ by\ 7\\\\ x=1\\\\ 2y=9-3x\ \ | divide\ by\ 2\\\\ y=\frac{9-3x}{2}=\frac{9-3*1}{2}=\frac{6}{2}=3[/latex]

Add answer